The city and cities in the stories, novels, essays and letters written by the Nobel Prize winner Ivo Andric - Шолак, З. (Актуальні проблеми слов’янської філології. Серія: Лінгвістика і літературознавство, 2010)
In his letters, essays stories and novels The Nobel Prize winner Ivo Andrić mentioned many
cities. He had visited a large number of them both at home and abroad and left behind his thoughts
regarding them. Amongst the cities we can find: Rome, Naples, Vienna, Graz, Bucharest, Krakow,
Athens, Istanbul, Paris, Lisbon, Berlin, Moscow, Leningrad, Beijing, Geneva, Marseilles, Copenhagen
and London. In his observations Andrić always tries to find the most important characteristics of cities or
he just presents certain interesting impressions lingering on some happenstance detail ha had come
across. Je always tried to provide not only explanations gotten from documents but also from other
sources and personal impressions in order to portrait events which had taken place in the cities linked to
his personal life: Travnik, Višegrad, Sarajevo and Belgrade.
Keywords: Ivo Andrić, city, novel, story, travel book. У своїх листах, есе, оповіданнях і романах лауреат Нобелівської премії Іво Андрич згадує
багато міст, які відвідав як на Батьківщині, так і за кордоном, і залишив після себе думки про них.
Згадуються такі міста, як: Рим, Неаполь, Відень, Грац, Бухарест, Краків, Афіни, Стамбул, Париж,
Лісабон, Берлін, Москва, Ленінград, Пекін, Женева, Марсель, Копенгаген і Лондон.
У спостереженнях Андрича видно, що він або намагається знайти найважливіші характеристики
міста, або просто представляє деякі цікаві враження про місця, на які випадково натрапив. Іво у
своїх роботах спирається не лише на документальний матеріал, а й на інформацію з інших
джерел, особисті враження, отримані від зображуваних подій, що відбувалися в містах,
пов’язаних з його життям: Травник, Вишеград, Сараєво та Белград.
Ключові слова: Іво Андрич, місто, роман, оповідання, путівник. В своих письмах, эссе, рассказах и романах лауреат Нобелевской премии Иво Андрич
вспоминает много городов, которые посетил как на Родине, так и за рубежом и оставил после
себя мысли о них. Упоминаются такие города, как: Рим, Неаполь, Вена, Грац, Бухарест, Краков,
Афины, Стамбул, Париж, Лиссабон, Берлин, Москва, Ленинград, Пекин, Женева, Марсель,
Копенгаген и Лондон. В наблюдениях Андрича видно, что он или пытается найти важнейшие
характеристики города, или просто представляет некоторые интересные впечатления о местах,
которые случайно посетил. Иво в своих работах опирается не только на документальный
материал, но и на информацию из других источников, личные впечатления, полученные от изображаемых событий, происходивших в городах, связанных с его жизнью: Травник, Вышеград,
Сараево и Белград.
Ключевые слова: Иво Андрич, город, роман, рассказ, путеводитель.